Cytoprotective autophagy induction by withaferin A in prostate cancer cells involves GABARAPL1 - Hahm, Eun-Ryeong (Mol Carcinog, 2020)
Withaferin A (WA) is a naturally-occurring steroidal lactone with proven cancer chemopreventive activity in preclinical models of different cancers including prostate adenocarcinoma. Previously we compared the RNA-seq data from control and WA-treated 22Rv1 human prostate cancer cells to identify mechanistic targets of this phytochemical. The gene ontology pathway analysis of the RNA-seq data revealed significant upregulation of genes associated with autophagy upon WA treatment in 22Rv1 cells. In this study, we extended these findings to investigate the mechanism underlying WA-induced autophagy. Initially, we confirmed autophagy induction by WA treatment by transmission electron microscopy using three prostate cancer cell lines (LNCaP, 22Rv1, and PC-3). Fourteen common genes altered by 8- and 16-hour exposure to WA were identified from human autophagy PCR array and these results were consistent with the RNA-seq data. Two key autophagy markers (LC3BII and SQSTM1) were robustly increased in WA-exposed LNCaP, 22Rv1, and PC-3 cells as determined by immunoblotting, and this effect was elevated in the presence of autophagy inhibitor bafilomycin A1. Bafilomycin A1 treatment augmented WA’s cytotoxicity and subsequently its proapoptotic potential. WA treatment induced GABARAPL1 (ATG8L) protein expression in all three cell lines and its knockdown by RNA interference attenuated WA-mediated apoptosis. WA-induced autophagy was not affected in the presence of an antioxidant (EUK134). Taken together, the present study reveals that WA-mediated autophagy is cytoprotective and mediated by GABARAPL1.